Implementation of Village Fund Policy To Realize Village Accountability and Resilience in Tangerang Regency - Sriyani, Sriyani; Akbar, Bahrulah; Achmad, Mansyur; Kusworo, Kusworo; Sunyoto, Edi (Universitas Muhammadiyah Ponorogo, 2024)
The Government's attention to development in rural areas has experienced quite significant developments, marked by allocations Village Fund budget which continues to increase and produce development facilities and infrastructure massively in villages. However, the implementation of village fund policies still does not provide an optimal contribution to handle the problem of poverty and improving village independence. The shift in development funding from the center to the regions encourages village officials to commit acts of corruption. This shows that accountability in village fund management and village resilience need to be improved. Although Tangerang Regency is very close to the national economic center, it still cannot create villages which are free from corruption and independent villages. This research aims to analyze policy implementation along with its obstacles in realizing accountability and resilience villages in Tangerang Regency. This study uses a qualitative approach. Study This finds (1) implementation policy management of village funds in Tangerang Regency is still not optimal (2) main obstacles for realizing accountable and independent Village Fund management villages in Tangerang Regency are (a) weak system monitoring and distribution of information Village Fund management; (b) weak resource man Village Fund Manager; and (c) low Village Original Income (PADesa) to total village and shopping income.